Stockholm3 - A new option to detect Prostate Cancer - Ali, Moosa Zulfiqar; Ahmad, Roshaan; Akmal, Amna (Journal of the Pakistan Medical Association, 2022)
Prostate cancer is the second most often diagnosed cancer and the sixth most prevalent cause of cancer mortality in males globally.1 It is usually screened by measuring prostate specific antigen (PSA) levels in the blood. However, the PSA test results in unnecessary biopsies, over-diagnosis, over-treatment, and higher expenses.2 The Karolinska Institutet in Stockholm, Sweden, developed the Stockholm3 test to overcome PSA test’s shortcomings. ---Continue